2020
DOI: 10.3390/ma13184026
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rh(I)/Ru(III) Bimetallic Catalyst Catalyzed Carbonylation of Methanol to Acetic Acid

Abstract: In this study, a Rh(I)/Ru(III) catalyst with a bimetallic space structure was designed and synthesized. The interaction between the metals of the bimetallic catalyst and the structure of the bridged dimer can effectively reduce the steric hindrance effect and help speed up the reaction rate while ensuring the stability of the catalyst. X-ray photoelectron spectroscopy (XPS) results show that rhodium accepts electrons from chlorine, thereby increasing the electron-rich nature of rhodium and improving the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Alternatively, Dutta reported that Rh­(I) complexes with quinolines and quinoline carboxaldehyde and carboxylic acid derivatives as ligands are also efficient catalysts for methanol carbonylation to form acetic acid and methyl acetate. , Soon after, the same group reported that Rh­(I) complexes with acetylpyridine ligands catalyze methanol carbonylation to acetic acid with a TON of 1581–1654 . Most recently, Ji and co-workers reported a bimetallic Ru–Rh catalyst, 14.10 , that is more stable than the Monsanto catalyst because of the interaction between Ru and Rh . The steric hindrance within the catalyst and its folded structure prevented deactivation over the reaction course, reaching a TOF of 32 million h –1 and a TON of 32 million.…”
Section: Molecular Catalysis For C–c Coupling Of C1 Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Dutta reported that Rh­(I) complexes with quinolines and quinoline carboxaldehyde and carboxylic acid derivatives as ligands are also efficient catalysts for methanol carbonylation to form acetic acid and methyl acetate. , Soon after, the same group reported that Rh­(I) complexes with acetylpyridine ligands catalyze methanol carbonylation to acetic acid with a TON of 1581–1654 . Most recently, Ji and co-workers reported a bimetallic Ru–Rh catalyst, 14.10 , that is more stable than the Monsanto catalyst because of the interaction between Ru and Rh . The steric hindrance within the catalyst and its folded structure prevented deactivation over the reaction course, reaching a TOF of 32 million h –1 and a TON of 32 million.…”
Section: Molecular Catalysis For C–c Coupling Of C1 Sourcesmentioning
confidence: 99%
“…125 Most recently, Ji and co-workers reported a bimetallic Ru−Rh catalyst, 14.10, that is more stable than the Monsanto catalyst because of the interaction between Ru and Rh. 126 The steric hindrance within the catalyst and its folded structure prevented deactivation over the reaction course, reaching a TOF of 32 million h −1 and a TON of 32 million. Under the same reaction conditions, the Monsanto catalyst showed a TOF of 7.6 million h −1 and a TON of 7.6 million.…”
Section: Molecular Catalysis For C−c Coupling Of C 1 Sourcesmentioning
confidence: 99%
“…[49][50][51][52][53][54] As one of the noble metals, Ru has been widely utilized in the catalysis of methanol carbonylation, olen metathesis, and other reactions. [55][56][57][58] Therefore, Ru has a broad prospect to be applied to the reversible reaction process of CO 2 . [59][60][61][62][63][64][65] Based on this, Chen et al 59 synthesized Ru nanoparticles and immobilized them on carbon nanotubes as cathode catalysts for Li-CO 2 batteries.…”
Section: Noble Metals and Their Composite Based Materialsmentioning
confidence: 99%